2011
DOI: 10.1152/ajpregu.00300.2010
|View full text |Cite
|
Sign up to set email alerts
|

Muscle oxidative capacity during IL-6-dependent cancer cachexia

Abstract: Many diseases are associated with catabolic conditions that induce skeletal muscle wasting. These various catabolic states may have similar and distinct mechanisms for inducing muscle protein loss. Mechanisms related to muscle wasting may also be related to muscle metabolism since glycolytic muscle fibers have greater wasting susceptibility with several diseases. The purpose of this study was to determine the relationship between muscle oxidative capacity and muscle mass loss in red and white hindlimb muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
204
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 134 publications
(213 citation statements)
references
References 61 publications
9
204
0
Order By: Relevance
“…In the present study, a reduction in the expression levels of COX IV and Cyto C was observed concomitantly with the downregulation of Mfn2. COX IV and Cyto C are proteins of the mitochondrial respiratory chain and their loss results in reduced ATP formation and mitochondrial dysfunction (11). Therefore, it is possible that cancer cachexia induces the downregulation of Mfn2 in skeletal muscle cells, leading to mitochondrial dysfunction and thereafter muscle mass loss.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In the present study, a reduction in the expression levels of COX IV and Cyto C was observed concomitantly with the downregulation of Mfn2. COX IV and Cyto C are proteins of the mitochondrial respiratory chain and their loss results in reduced ATP formation and mitochondrial dysfunction (11). Therefore, it is possible that cancer cachexia induces the downregulation of Mfn2 in skeletal muscle cells, leading to mitochondrial dysfunction and thereafter muscle mass loss.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of mitochondrial fission has been shown to inhibit muscle loss during fasting (11,15). In addition, downregulation of Mfn2 has been observed in the muscle of obese and non-obese type 2 diabetic subjects (16,17), and decreased mRNA expression levels of Mfn2 were observed in the skeletal muscle of tumor-bearing mice with severe cachexia (11). These results suggested that Mfn2 is involved in muscle wasting associated with diseases such as cancer cachexia.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations